The Highlander's kilted bride - Kelly, Vanessa (Kelly, Vanessa. Clan Kendrick., 2023)
When he is reunited with tomboy Charlotte Stewart at the wedding of her younger sister, highlander-and spy-Kade Kendrick is distracted by rival suitors, a dangerous mission and this unconventional woman who embodies all his desires.